2008
DOI: 10.1063/1.2956999
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic polarization of quantum vortices in He II

Abstract: The weak magnetic polarization which a quantum vortex in a superfluid Bose liquid acquires as a result of the mutual electric polarization of atoms and the nonuniform distribution of the atomic density in its core is discussed. A rectilinear single-quantum vortex carries a magnetic moment directed along and proportional to the length of the vortex line. The magnetic moment density per unit length and the corresponding quantum of magnetic flux (vortex fluxoid) are directly related with the quantum circulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
1
10
1
Order By: Relevance
“…Comparing our EFT result (16) and the result (2) of our earlier discussion based on the flexo-electric effect, one sees that the two expressions (for dilute systems where ∆n ≈ n ≈ n s ) coincide when the undetermined…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Comparing our EFT result (16) and the result (2) of our earlier discussion based on the flexo-electric effect, one sees that the two expressions (for dilute systems where ∆n ≈ n ≈ n s ) coincide when the undetermined…”
supporting
confidence: 64%
“…More generally, any configuration with the topology of a superfluid vortex will necessarily carry a non-vanishing magnetic flux. A configuration of ν well-separated vortices will have total flux which is just ν time the minimal value (16).…”
mentioning
confidence: 99%
“…The experiments of Ref. [3,4] stimulated a large number of theoretical studies and suggested various theoretical explanations for this phenomenon [5,6,7,8,9,10,11,12]. For instance, in Ref.…”
Section: Introductionmentioning
confidence: 98%
“…One possible way to describe microscopically the observed effects is the application of Zubarev's method to these systems (phenomenological approaches to the problem can be found in the theoretical studies Refs. [7][8][9][10][11][12][13][14][15][16]. For dilute Bose systems, for which a consistent microscopic theory can only be built, the main result can be obtained by replacing the field operators in the i-th excited state with C-numbers.…”
Section: Introductionmentioning
confidence: 99%